Exploring unconventional σ-hole interactions: computational insights into the interaction of XeO3 with non-aromatic coordinating solvents - Dash, Soumya Ranjan; Vanka, Kumar (Chemphyschem, 2024)
In order to control the explosiveness and shock sensitivity of XeO3, we have investigated its plausible interaction with various non-aromatic coordinating solvents, serving as potential Lewis base donors, through density functional theory (DFT) calculations. Out of twenty six such solvents, the top ten were thus identified and then thoroughly examined by employing various computational tools such as the mapping of the electrostatic potential surface (MESP), Wiberg bond indices (WBIs), non-covalent interaction (NCI) plots, Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, and the energy decomposition analysis (EDA). The amphoteric nature of XeO3 was also explored by investigating the extent of back donation from the lone pair of Xe to the antibonding orbital of the donating atom/group of the solvent molecules. The C-H & mldr;O interactions were also found to be a contributing factor in the stabilization of these adducts. Although these aerogen-bonding interactions were found to be predominantly electrostatic, significant contributions from the orbital contributions, as well as dispersion interactions, were observed. The top three non-aromatic solvents (among the twenty six studied) which form the strongest adducts with XeO3 are proposed to be hexamethylphosphoramide (HMPA), N,N `-dimethylpropyleneurea (DMPU) and tetramethylethylenediamine (TMEDA).
Keywords: Aerogen bonding; Non-Aromatic Solvents; non-covalent interactions; Sigma-hole; XeO3